2022
DOI: 10.1371/journal.pcbi.1009981
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile contractions and pattern formation in excitable actomyosin cortex

Abstract: The actin cortex is an active adaptive material, embedded with complex regulatory networks that can sense, generate, and transmit mechanical forces. The cortex exhibits a wide range of dynamic behaviours, from generating pulsatory contractions and travelling waves to forming organised structures. Despite the progress in characterising the biochemical and mechanical components of the actin cortex, the emergent dynamics of this mechanochemical system is poorly understood. Here we develop a reaction-diffusion mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
(124 reference statements)
2
22
0
Order By: Relevance
“…While in some cases, the function of the pulsatile dynamics is unclear, in other cases the pulsatile dynamics are essential, enabling large-scale force generation while maintaining tissue integrity 8,9 , and facilitating cellular functions such as active transport and motility 6 . Typically, these periodic or aperiodic waves emerge from complex nonlinear reactions in coupled mechano-chemical systems, involving regulators of the actomyosin machinery such as Rho GTPases 10,11,36,39,40 . Our work shows that waves can also emerge in essentially mechanical systems, with turnover but without complex biochemical regulation.…”
Section: Discussionmentioning
confidence: 99%
“…While in some cases, the function of the pulsatile dynamics is unclear, in other cases the pulsatile dynamics are essential, enabling large-scale force generation while maintaining tissue integrity 8,9 , and facilitating cellular functions such as active transport and motility 6 . Typically, these periodic or aperiodic waves emerge from complex nonlinear reactions in coupled mechano-chemical systems, involving regulators of the actomyosin machinery such as Rho GTPases 10,11,36,39,40 . Our work shows that waves can also emerge in essentially mechanical systems, with turnover but without complex biochemical regulation.…”
Section: Discussionmentioning
confidence: 99%
“…When we substitute this into equation (15), the eigenvalue λ can be calculated. Before doing so however, we first distinguish two cases: (i) equal relaxation times τ B = τ S and (ii) unequal relaxation times τ B ̸ = τ S .…”
Section: Linear Stability Analysismentioning
confidence: 99%
“…The dominant eigenvalue corresponds to the mode with k 2 = 4π 2 /L 2 . For the second case with τ B ̸ = τ S , substituting equation (19) into equation (15) results in a quadratic equation for the eigenvalues. We will write this as αλ 2 + βλ + γ = 0, with the coefficients α, β, γ defined as…”
Section: Linear Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, previous studies showed that pulsatile oscillatory time dynamics is an important feature of many morphogenetic processes [11,12,13]. Theoretical models could reproduce pulsatile patterns in active gels by i) incorporating at least two molecular species and nonlinearities in their mechanochemical regulation [14,15,16], or by ii) combining active hydrodynamics with the dynamics of a polarization vector field [17,18], by iii) coupling an axisymmetric viscoelastic active surface with a surrounding highly viscous fluid [19].…”
Section: Introductionmentioning
confidence: 99%